Cassava Utilization Program as An Innovation to Make Getuk Gulung to Increase The Selling Value - Desi Rahmawati; M Komarudin (Journal of Islamic Economy and Community Engagement, 2021)
The purpose of community service, is done so that people can use cassava into product innovation that has a sale value, so that it can increase the income of the people of Padamulya Village. The minimum performance indicator has an understanding to utilize cassava into product innovation. The target of the cassava utilization program as an innovation in getuk gulung products is the people of Padamulya Village, Especially Padamulya Village. The method used in this community service is counseling and workhop (training) methods, about the procedures for making product innovations from cassava such as getuk gulung si engkong. The results of community service activities are that the community has enthusiasm in knowing and gaining knowledge about cassava product innovation, it can be seen from the large number of participants participating in the training and the community wanting to follow up on the existence of business group programs and making Getuk Gulung as a superior product in Padamulya Village.Keywords: Product Innovation, Cassava, Community Service